The Engine Performance Characteristics of an IDI Diesel Engine Fueled by Soybean Oil Methyl Esters - S K Keun; A Ghurri (Journal of Engineering and Scientific Research, 2019)
An experimental investigation was conducted to evaluate the performance of an indirect injection (IDI) diesel engine using diesel(D100) and diesel-biodiesel blends (BD25, BD45, BD65) separately. The engine was run in various engine loads at constant engine speed ranging from 1000 to 2400 rpm with an interval 200 rpm. The results showed that the biodiesel content decreased the engine torque and power. This might be mainly affected by the lower LHV of the biodiesel, and also the worse combustion due to higher density of the biodiesel compared to the diesel fuel. The loss of power due to lower heating value of biodiesel were notas high as the difference in their heating value that might be down to the better lubricity of biodiesel as proved in the higher brake thermal efficiency and mechanical efficiency when using the biodiesel blends. The brake specific fuel consumption is higher with the increase of biodiesel content but the diesel fuel delivered the highest energy to run the engine. The maximum pressure inside cylinder and the heat release rate of D100 is slightly higher than those of biodiesel blends. Keywords: diesel engine, biodiesel, engine performance, emission.